Efficient Scheme for Implementing the Deutsch-Jozsa Algorithm in Cavity QED (Journal of Atomic and Molecular Sciences, 2013)
A scheme is proposed for implementing a two-qubit quantum logic gate and realizing the Deutsch-Jozsa algorithm in cavity QED. In the scheme a three-level atom interacts with highly detuned cavity modes. The gate is not affected by the atomic decay rates because of the metastable lower levels are involved in the gate operations. The Deutsch-Jozsa algorithm is easily realized with current experimental techniques.